RNA interference‐mediated phosphodiesterase 4D splice variants knock‐down in the prefrontal cortex produces antidepressant‐like and cognition‐enhancing effects. (24th January 2013) - Wang, Zhen‐Zhen; Zhang, Yi; Liu, Yan‐Qin; Zhao, Nan; Zhang, You‐Zhi; Yuan, Li; An, Lei; Li, Jing; Wang, Xiao‐Yun; Qin, Juan‐Juan; Wilson, Steven P; O'Donnell, James M; et al.
Abstract : Background and Purpose: Phosphodiesterase 4 (PDE4) inhibitors produce potent antidepressant‐like and cognition‐enhancing effects. However, their clinical utility is limited by the major side effect of emesis, which appears to be PDE4 isoform‐specific. Although PDE4D subtype plays the pivotal role in these therapeutic profiles, it is also the primary subtype responsible for emesis. Therefore, the aim of present research was to investigate whether long‐form PDE4D variants mediate antidepressant‐like and cognition‐enhancing effects, but are irrespective with emesis. Experimental Approach: In mice microinfused with lentiviral vectors that contained shRNA‐mir hairpin structure targeting long‐form PDE4Ds into bilateral prefrontal cortices, the tail‐suspension and forced‐swim tests were used to measure antidepressant‐like effects; novel object recognition and Morris water‐maze tasks were used to determine cognition‐enhancing effects. The emetic potential was assessed by alpha2 adrenergic receptor‐mediated anaesthesia, a surrogate measure of emesis. Intracellular cAMP signalling was analysed by time‐resolved FRET immunoassay and Western‐blot. Dendritic complexity was assessed by Golgi staining. Key Results: Microinfusions of lentiviral PDE4D‐shRNA down‐regulated PDE4D4 and PDE4D5, and imitated the antidepressant‐like and cognition‐enhancing effects of the prototypical PDE4 inhibitor rolipram. The behavioural effects were related to dendritic complexity and mediated by the increased cAMP signalling. In addition, these effects were not enhanced in the presence of rolipram. Finally, while rolipram shortened the duration of combined anaesthesia, RNA interference‐mediated PDE4D knock‐down in the prefrontal cortex did not. Conclusion and Implications: These data suggest that long‐form PDE4Ds, at least PDE4D4 and PDE4D5, may be the promising targets for the development of PDE4 variant‐selective inhibitors as the new pharmacotherapies for depressive disorders and neurodegenerative diseases involving memory deficits.